Civil avionics systems - Moir, I. (Ian) (AIAA education series)
This book introduces the reader to an industry that has to deal with issues that are complex and sophisticated, market and technology driven, safety conscious, high integrity, and environmentally influenced. The civil avionics industry is driven by market factors and trends in public mobility, global business travel, and domestic leisure needs. World finances, terrorist activity, political pressure, or public loss of confidence resulting from a perception of poor safety also drives the industry. The text covers all aspects of civil avionics systems including the technology, systems development, electronics, sensors, communication and guidance aids, displays, controls, and systems integration. It further discusses future air navigation systems and military applications.